Effect of Different Green Extraction Methods and Solvents on Bioactive Components of Chamomile (Matricaria chamomilla L.) Flowers - Jana Šic Žlabur; Ivanka Žutić; Sanja Radman; Maja Pleša; Mladen Brnčić; Francisco J. Barba; Gabriele Rocchetti; Luigi Lucini; Jose M. Lorenzo; Rubén Domínguez; Suzana Rimac Brnčić; Ante Galić; et al. (Molecules, 2020)
Chamomile (Matricaria chamomilla L.) dried flowers contain a group of interesting biologically active compounds such as sesquiterpenes, flavonoids, coumarins, vitamins, phenolic acids and glucosides. Therefore, the aim of the present study was to characterize the composition in bioactive compounds (specialized metabolites) present in water and ethanol extracts of chamomile flowers, together with monitoring the impact of different extraction techniques (conventional vs. ultrasound-assisted extraction (UAE)) on the parameters under investigation. UAE treatment significantly decreased the extraction time of bioactive compounds from herbal material. Polyphenolic compounds content and antioxidant capacity were significantly higher in UAE extracts. Moreover, solvent type had a significant impact on the specialized metabolites content, while the highest vitamin C and polyphenols content were recorded in 50% ethanol (v/v) extracts. Optimization of basic extraction factors: solvent type, temperature and technique is crucial for obtaining the extracts with the highest content of specialized metabolites and antioxidant capacity.